A survey of Indian women living with concurrent complications of polycystic ovarian syndrome and pre-menopause in their pre-menopausal stage - Kumaravelu, Ranjane; Dhevi, Bharathi; Thulasi, Arun (International Journal Of Community Medicine And Public Health, 2025)
Background: Polycystic ovary syndrome (PCOS), a widespread endocrine disorder, is particularly prevalent among working women in tier 2 cities in India. Clinical guidelines in India do not adequately consider morbidities involving PCOS and pre-menopause when diagnosing and caring for women with PCOS. This study aimed to understand the dependency on medication, alternate treatments, yoga, and combined comorbidities of PCOS, key concerns, quality of life (QoL), and diagnosis experiences of working Indian women living with PCOS. Methods: A comprehensive physical and online survey was conducted among working women of pre-menopausal age living with PCOS in Tamil Nadu. The study examined treatment modalities, symptoms, and their interrelationships. Results: The study included 91 participants with a mean age of 35-55 years, focusing on women in their pre-menopausal period. A significant positive correlation was found between PCOS and pre-menopause (PM) (r=0.380, p<.001), indicating a strong interrelationship between these conditions. The study revealed significant correlations between PCOS and pre-menopausal symptoms, with 45.06% of participants reporting moderate to severe impact on daily life. Conclusions: The findings highlight the need for comprehensive management strategies, considering the strong correlation between PCOS and pre-menopause (r=0.380, p<0.001). The data suggests that while medication remains the primary treatment modality, there is potential in incorporating complementary approaches such as yoga and alternative treatments.